2008
DOI: 10.2217/17460794.3.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Binding Lectin in HIV Infection

Abstract: Infection with HIV represents a significant global health problem, with high infection rates and high mortality worldwide. Treatment with antiretroviral therapy is inaccessible to many patients and efficacy is limited by development of resistance and side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 54 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…The lectin pathway is homologous to the classical pathway; however, it is activated by mannose-binding lectin (MBL) or ficolin, as well as several MBL-associated serine proteases (MASPs), rather than the C1 complex [17]. MBL and ficolin ligands are abundant in the cell walls of various pathogens, including bacteria, yeast, fungi, and viruses [17][18][19]. Binding of MBL or ficolin to its ligands activates the MASPs, which then induce C4 and C2 cleavage, leading to C3 activation in the same manner as that described for the classical pathway.…”
Section: Complement Systemmentioning
confidence: 99%
“…The lectin pathway is homologous to the classical pathway; however, it is activated by mannose-binding lectin (MBL) or ficolin, as well as several MBL-associated serine proteases (MASPs), rather than the C1 complex [17]. MBL and ficolin ligands are abundant in the cell walls of various pathogens, including bacteria, yeast, fungi, and viruses [17][18][19]. Binding of MBL or ficolin to its ligands activates the MASPs, which then induce C4 and C2 cleavage, leading to C3 activation in the same manner as that described for the classical pathway.…”
Section: Complement Systemmentioning
confidence: 99%
“…A schematic illustration of this process is shown in Figure 1. It has been reported that mannosebinding lectins may play a key role in determining host susceptibility and variability of responses to infection, pathogenesis and progression of disease in HIV patients (168) and neutropenia (167). It also plays a critical role in the innate immunity against infections caused by yeasts by increasing uptake by polymorphonuclear cells (169).…”
Section: Cell Recognitionmentioning
confidence: 99%
“…MBL is an acute phase, multimeric protein (with six 96 kDa subunits) of hepatic origin and belongs to the family of collectins (Eisen et al, 2008;Garred et al, 1997). MBL acts as a pattern recognition molecule and binds to carbohydrate structures of invading pathogens.…”
Section: Mannose-binding Lectin (Mbl)mentioning
confidence: 99%
“…In HIV infection, MBL is known to bind to envelope viral protein subunits gp120 and gp41. Both these proteins have oligosaccharide side chains of high-mannose type; gp120 in particular is highly glycosylated, with a high proportion of mannosecontaining oligosaccharides (Eisen et al, 2008). MBL-HIV interaction enhances opsonisation and initiate viral killing (Eisen et al, 2008).…”
Section: Mannose-binding Lectin (Mbl)mentioning
confidence: 99%
See 1 more Smart Citation